Expenditure and Employment Data for the Criminal Justice System (United States): CJEE Extracts File, 1990 ([Verlag nicht ermittelbar], 1993)
These criminal justice expenditure and employment (CJEE) data are taken from a special compilation of sources available from the Census Bureau's Annual Surveys of Governments, Finance Statistics and Employment Statistics. Levels of government covered are federal, state, county, municipal, and towns and townships. Information is included on total employment, total police protection, police protection with arrest powers, other police protection, judicial-legal employment, corrections employment, total expenditures, police protection expenditures, judicial-legal expenditures, and corrections expenditures. Types of expenditures include direct current, capital outlay, equipment, and intergovernmental. Types of employment include total, full-time, part-time, and full-time equivalent.